Lord Acton and Poland (Economic and Political Thought, 2016)
With one exception, Lord Acton did not write anything that is entirelydevoted to Poland. On the other hand, the Polish Lithuanian Commonwealthand Poland in general are mentioned many times in his writing. The articlecollects those scattered remarks and attempts to explore Lord Acton’sviews on Poland, beginning with Poland’s origins in the tenth century andending with the January Uprising of 1863. The conclusions are somewhatdisappointing and surprising. Knowing Polish history in detail, Lord Actondid not go beyond standard Western clichés about it, proving he did notreflect much on the nature of gentry’s democracy and Polish liberties. Themost surprising of his views on the uprising, in turn, is his cold, realpolitikapproach, far from his usual dogmatic love of civic liberty. In this respect,the article in a way revises what we have known so far about Acton’s theoryof liberty and his view on liberalism.